2022
DOI: 10.3390/agronomy12061431
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Protein from High-Protein Rice on Gelatinization and Retrogradation Properties in High- and Low-Amylose Reconstituted Rice Flour

Abstract: High-protein rice is nutritional, but its taste attributes are inferior to low-protein rice. Many documents correlate its taste attributes with its gelatinization and retrogradation properties. This study investigated the changes in gelatinization and retrogradation properties of low- and high-amylose reconstituted rice flour (RRF) added with different fractions of proteins extracted from high-protein rice. The addition of protein decreased the RVA (rapid viscosity analyzer) viscosity parameters of the RRF but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Regardless of the limewater soaking treatment, KDML105 had a lower amylose content (19.5% dry wt) than the commercial rice flour (31% dry wt), which can also be related to the weaker (lower firmness and consistency) gel (Table 4). Rice flour containing higher amylose produced firmer (harder) gel than that containing low amylose (Zhao et al ., 2022). On the other hand, the magnitude of cohesiveness and an index of viscosity of gel showed the opposite trend of the firmness and consistency (Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regardless of the limewater soaking treatment, KDML105 had a lower amylose content (19.5% dry wt) than the commercial rice flour (31% dry wt), which can also be related to the weaker (lower firmness and consistency) gel (Table 4). Rice flour containing higher amylose produced firmer (harder) gel than that containing low amylose (Zhao et al ., 2022). On the other hand, the magnitude of cohesiveness and an index of viscosity of gel showed the opposite trend of the firmness and consistency (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Zhao et al . (2022) revealed that the gelatinisation temperature of rice flour was influenced by the type, granule size, shape, and non‐starch components such as, protein and lipids, which affected the heat transfer hindrance for starch gelatinisation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the early stages of GSHE hydrolysis, the increase in very short chains in amylopectin reduced the cross-linked interactions between starch components [49]. In addition, rice protein in the RF group inhibited starch swelling, playing a significant role in the viscosity drop [50]. With the continuation of hydrolysis, the relative content of DP > 6 components, especially the DP > 36 components (Table 4) which were regarded as the backbone of amylopectin, increased, promoting cross-linking interactions between starch molecules [51].…”
Section: Pasting Behaviormentioning
confidence: 99%
“…It is hypothesized that starch-protein interactions are strengthened when stored at −18 °C, as it has been reported that the electrostatic and hydrogen bonding interactions between amylose and protein significantly decrease the ΔH but increase melting temperatures. [41][42][43] Also, removal of these endogenous proteins decreases in the starch thermal stability of adlay seed. 44…”
Section: Inter-and Intramolecular Interactions Measured By Dscmentioning
confidence: 99%